2021
DOI: 10.3390/pharmaceutics13111871
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on Inhibition of Pancreatic Cancer Cells by Resveratrol Gold Nanoparticles and a Resveratrol Nanoemulsion Prepared from Grape Skin

Abstract: Resveratrol, a phenolic compound possessing vital biological activities such as anti-cancer, is present abundantly in grape skin, a waste produced during the processing of grape juice. The objectives of this study were to prepare resveratrol-gold nanoparticles and a resveratrol nanoemulsion from grape skin and study their inhibition effects on pancreatic cancer cells BxPC-3. The spherical-shaped citrate gold nanoparticles (GNPs) and resveratrol-gold nanoparticles (R-GNPs) were, respectively, prepared with a su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…The synthesized AuNPs have absorption peaks at a wavelength of 520 nm, while the spectral trace of DOX alone shows a typical absorption peak at 490 nm. Similar findings were reported for AuNPs (20.8 nm) by Inbaraj et al [ 57 ] showing the maximum absorbance of the SPR peak to be 538 nm, and for DOX by Li et al [ 58 ] indicated the ultraviolet absorption peak to be 480 nm. The absorption spectrum of free DOX does not interfere with AuNPs, and the characteristic peak of AuNP at 520 nm has shifted to 490 nm, due to doxorubicin in synthesized Au‐PEI‐HA‐DOX particles.…”
Section: Resultssupporting
confidence: 87%
“…The synthesized AuNPs have absorption peaks at a wavelength of 520 nm, while the spectral trace of DOX alone shows a typical absorption peak at 490 nm. Similar findings were reported for AuNPs (20.8 nm) by Inbaraj et al [ 57 ] showing the maximum absorbance of the SPR peak to be 538 nm, and for DOX by Li et al [ 58 ] indicated the ultraviolet absorption peak to be 480 nm. The absorption spectrum of free DOX does not interfere with AuNPs, and the characteristic peak of AuNP at 520 nm has shifted to 490 nm, due to doxorubicin in synthesized Au‐PEI‐HA‐DOX particles.…”
Section: Resultssupporting
confidence: 87%
“…Nanotechnology approaches have been broadly utilized to obtain better solubility, enhance oral bioavailability, increase stability, and regulate the release of resveratrol. The resveratrol nanoparticles have markedly improved anticancer properties of resveratrol both in vitro and in vivo, indicating this approach as a potential strategy against various cancers [ 98 , 215 , 216 , 217 ]. González-Sarrías et al [ 217 ] showed that milk-derived exosomes (EXO) as nanocarriers can increase the bioavailability and anticancer activity of curcumin and resveratrol in breast tissue by increasing their antiproliferative activity, induction of apoptosis, cell cycle alteration, and caspase activation, even at nanomolar concentrations.…”
Section: Molecular and Cellular Targets Of Propolis And Its Flavonoid...mentioning
confidence: 99%
“…Many lines of evidence suggest that immunomodulation by propolis and its polyphenolic/flavonoid components is an important contributing factor to the antitumor and antimetastatic activities of these compounds. Flavonoids may induce the immune system [ 3 , 16 , 17 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 92 , 214 , 215 , 216 , 217 , 218 , 220 , 221 , 222 , 223 ], and act as powerful free radical scavengers [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 39 , 40 , 41 , 42 , 58 , 63 ]. Accordingly, a high dietary intake of flavonoids from propolis is associated with a reduced risk of cancer at different anatomical sites [ 3 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Antitumor Activity Of Propolis and Its Polyphenolic/flavonoi...mentioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion, Res-AuNPs enhanced phytochemical drug carrier capabilities as a potential application for cancer therapy ( Thipe et al, 2019 ). Furthermore, Res-AuNPs and Resveratrol-nanoemulsion inhibited the growth of BxPC-3pancreatic cancer cells and altered cell cycle regulation and apoptotic events ( Inbaraj et al, 2021 ).…”
Section: Tumor Cells Targeting By Nanoparticlesmentioning
confidence: 99%